2015
DOI: 10.1183/13993003.02278-2014
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in adult-onset asthma: results from the Swiss SAPALDIA cohort study

Abstract: A higher incidence of asthma is reported in women compared with men, but evidence in later adulthood is limited. We aimed to determine the 20-year cumulative incidence of adult asthma in Switzerland and its relation to sex, taking into account age and allergic sensitisation.We assessed incidence of self-report of doctor-diagnosed asthma between 1991/1992 and 2010/2011 in 5128 subjects without asthma, aged 18-60 years at baseline. The age-related probability of asthma onset was analysed by logistic regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 38 publications
3
28
1
Order By: Relevance
“…24,25 Self-reported nasal allergy was an overall risk factor for incident asthma. 12 This is consistent with our findings, where males with asthma were sensitized to a greater extent than females. In males, but not females, Atopy was a risk factor, although these results must be interpreted with caution due to the few incident cases.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…24,25 Self-reported nasal allergy was an overall risk factor for incident asthma. 12 This is consistent with our findings, where males with asthma were sensitized to a greater extent than females. In males, but not females, Atopy was a risk factor, although these results must be interpreted with caution due to the few incident cases.…”
Section: Discussionsupporting
confidence: 93%
“…9,10 Several studies have shown gender differences in incidence, prevalence, diagnosis and severity of asthma, 11,12 and also differences in perception and behavior are described. 9,10 Several studies have shown gender differences in incidence, prevalence, diagnosis and severity of asthma, 11,12 and also differences in perception and behavior are described.…”
Section: Introductionmentioning
confidence: 99%
“…A higher incidence of asthma among females in the adult population is described, [5][6][7] yet our figures are higher than generally reported. We are a tertiary level facility, and preferentially follow up patients whose asthma is difficult to control.…”
Section: Discussioncontrasting
confidence: 55%
“…Because of the gender differences in asthma onset and respiratory symptoms (Hansen et al, 2015;Takeda et al, 2013), we stratified the allele frequencies and genotypes by gender. However, no statistically significant differences in genotype or allele frequency distribution were found for rs2228145 and rs12083537 between patients and controls in either males or females (supporting Tables 1 and 2).…”
Section: The Genotype and Allele Frequency Distributions In Patients mentioning
confidence: 99%